Prevalence of Tuberculosis in Brazil: An epidemiological study (Research, Society and Development, 2025)
Tuberculosis (TB) is an infection caused by Mycobacterium tuberculosis, a bacillus predominantly transmitted through aerosols, which has negatively impacted human health since the dawn of humanity. This disease is directly associated with socioeconomic factors such as poverty, malnutrition, overcrowding, and immunosuppressive conditions, reflecting social inequalities. Since Robert Koch discovered its infectious nature in 1882, tuberculosis has been the subject of in-depth studies that have significantly advanced the understanding of its natural history and pathophysiology. Despite these advances, tuberculosis remains a persistent global public health challenge, especially in developing countries. The treatment, which is affordable and low-cost, can be effective, but its interruption or abandonment often leads to severe complications. Methodology: This study analyzed the prevalence of tuberculosis cases across the five regions of Brazil between 2013 and 2023. The data used were obtained from the Department of Informatics of the Unified Health System (DATASUS), taking into account regional variations and their impacts on public health. Objective: The main objective is to propose improvements in the management of tuberculosis cases, taking into account the specificities of each Brazilian region, as well as the need for more effective public policies. Results: During the evaluated period, all Brazilian regions showed an increase in tuberculosis cases. The growth rates were as follows: North 59%, Northeast 24%, Southeast 29%, South 19%, and Midwest 28%, highlighting the need for region-specific strategies and continuous investments in public health.